Application of project management tools in engineering services companies: Four case studies (2018)
A methodological proposal is designed for the planning of the scope, time and cost that strengthens the management of the projects developed by the services companies of Cúcuta and its metropolitan area. In the first phase, a descriptive study was carried out based on a maturity diagnosis which included the relevant tools to measure the culture in the planning of the scope, time and cost of the projects, which was validated by experts in PMI and applied in thirty companies to the officers who are in charge of the management of the projects. The second stage consisted in the selection of fifteen tools and techniques of the scope, time and cost management of the PMBOK Guide applicable in the methodological proposal according to the diagnosis. Finally, methodological guidelines for project management were designed in four social services companies, technology and computer science and civil constructions in which the tools defined in the proposal were incorporated, which will become guidelines for the execution of the projects guaranteeing the fulfilling of the deliverables, in the estimated time and with the assigned budget.